2017
DOI: 10.1108/jocm-10-2016-0218
|View full text |Cite
|
Sign up to set email alerts
|

Examining the roles of shared vision and career growth opportunity in developing new employees

Abstract: Purpose The purpose of this paper is to explore the relationship between career growth opportunity (CGO), well-being and turnover intention of new employees, and also probe into the moderating role of shared vision (SV) in organizations. Design/methodology/approach In total, 253 new employees participated in this study, and the partial least squares analysis was adopted to analyze the data. Findings The study findings have indicated that CGO will play a key role in determining emotional exhaustion (EE) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 25 publications
3
11
0
Order By: Relevance
“…First, our findings revealed that employees experienced a range of career management practices. This supports previous studies conducted in Sri Lanka such as Wickramasinghe and Jayaweera (2011) and also in Asia such as Huang et al (2017), Nawaz and Pangil (2016), Wang et al (2014) and Singh and Vohra (2009). Second, our findings showed that OCMPs significantly positively predict career growth by way of financial rewards and recognition and career goal achievement.…”
Section: Contribution Of the Findings For The Literaturesupporting
confidence: 90%
See 2 more Smart Citations
“…First, our findings revealed that employees experienced a range of career management practices. This supports previous studies conducted in Sri Lanka such as Wickramasinghe and Jayaweera (2011) and also in Asia such as Huang et al (2017), Nawaz and Pangil (2016), Wang et al (2014) and Singh and Vohra (2009). Second, our findings showed that OCMPs significantly positively predict career growth by way of financial rewards and recognition and career goal achievement.…”
Section: Contribution Of the Findings For The Literaturesupporting
confidence: 90%
“…Second, our findings showed that OCMPs significantly positively predict career growth by way of financial rewards and recognition and career goal achievement. In this regard, Karavardar (2014) in the context of Turkey showed that remuneration growth has strong negative influence on turnover intention; similar observations were also made by Huang et al (2017), Chen et al (2016) and Nawaz and Pangil (2016) in the context of Asia. Although these previous studies commented on CMPs and subsequent benefits for individuals, none of these has specifically investigated the association between OCMPs and career growth.…”
Section: Contribution Of the Findings For The Literaturesupporting
confidence: 74%
See 1 more Smart Citation
“…In addition to the independent effects of social mission and shared vision, we propose that the effects of employees' perceived social mission on meaning of work would be augmented if their perception of shared vision is high in social enterprises. With a strong sense of shared vision, employees perceive and communicate the positive aspects of a given environment (Huang et al, 2017). Employees also shape a common purpose and goals with colleagues (Kirkman and Rosen, 1999), and clearly understand the values the organization pursues (Berson et al, 2015;Pearce and Ensley, 2004).…”
Section: The Moderating Role Of Shared Visionmentioning
confidence: 99%
“…Career growth opportunities differ from career growth in that the former focuses on the chances of career development and advancement while the latter emphasizes the development and advancement obtained so far (Table 9). Prior research has construed variables such as extra-role performance, work engagement (Weer and Greenhaus, 2020), organizational citizenship behavior (Kwan, 2013) as antecedents and turnover intentions (Huang et al, 2017;Ohunakin et al, 2018) and perceived organizational support (Sumathi et al, 2015) as consequences of career growth opportunities. While a few authors have operationalized career growth opportunities with the measures of organizational career growth through career goal progress, promotion speed, professional ability development and remuneration growth (Bashir et al, 2020;Wanniarachchi et al, 2020), others have considered structural and content dimensions of career growth opportunities (Weer and Greenhaus, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%